Anti-inflammatory effects of curcumin are associated with down regulating microRNA-155 in LPS-treated macrophages and mice. (1st January 2017) - Ma, Feiya; Liu, Fei; Ding, Liang; You, Ming; Yue, Huimin; Zhou, Yujie; Hou, Yayi
Abstract: Context: The natural polyphenolic compound curcumin has been proved to modulate innate immune responses and possess anti-inflammatory properties. Nevertheless, the mechanism remains poorly understood, particularly regarding curcumin-regulated miRNAs under inflammatory response. Objective: This study investigates the role of miRNA-155 in the effects of curcumin on inflammatory response in cell and a mouse model. Materials and methods: The anti-inflammatory activity of curcumin (5, 10 and 15 μM, 2 h) in lipopolysaccharide (LPS, 200 ng/mL)-induced cells were measured by quantitative PCR. The animals were treated orally by 20 mg/kg curcumin for 3 days before an LPS intraperitoneal injection (10 mg/kg, 16 h). MicroRNA (miRNA) expression and the underlying molecular mechanisms were assessed using transfection technique and western blotting. Results and discussion: Curcumin efficiently inhibited LPS-induced cytokines (TNF-α, IL-6) and microRNA-155 (miR-155) expression ( p < 0.05) without affecting the normally growth of Raw264.7 and THP-1 cells (IC50 21.8 and 22.3 μM at 48 h, respectively). Moreover, the levels of cytokines were suppressed by curcumin in miR-155 mimics transfected cells ( p < 0.05). A blockade of PI3K/AKT signalling pathways resulted in a decreased level of miR-155 ( p < 0.05). Curcumin effectively protected mice from sepsis as evidenced by decreasing histological damage, reducing AST (352.0 vs 279.3 U/L), BUN (14.8 vs 10.8 mmol/L) levels and the proportion of macrophages in spleen (31.1% vs 13.5%). MicroRNA-155 level and cytokines were also reduced in curcumin-treated mice ( p < 0.05). Conclusions: Curcumin's ability to suppress LPS-induced inflammatory response may be due to the inhibition of miR-155.